Building Social Trust: A Human Capital Approach - HUANG, Fali (Institutional Knowledge at Singapore Management University, 2007)
Much evidence suggests individuals differ in their predisposition to cooperate, which is essentially a component of human capital. This paper examines the role of individual cooperative tendencies and their interactions with institutions in generating social trust; it also endogenizes cooperative tendencies using a human-capital investment model. Multiple equilibria and inefficiencies exist due to positive externalities. An innovative finding is that, when institutions are more effective in punishing defecting behaviors, more people invest in cooperative tendencies and hence the endogenous social trust is higher, though the equilibrium cooperative tendencies are lower. This paper provides a plausible explanation for many empirical and experimental results.